Hall technique for primary teeth: A systematic review and meta-analysis. (November 2022) - Hu, Shijia; BaniHani, Alaa; Nevitt, Sarah; Maden, Michelle; Santamaria, Ruth M.; Albadri, Sondos
Abstract: Background: There has been a debate about the use of Hall Technique (HT), whether it can be considered as a standard technique for the management of carious primary molars. Aim: To summarise the evidence on HT for managing dentine caries in primary teeth. Design: MEDLINE, Embase, CENTRAL and Epistemonikos databases were searched for clinical studies conducted from 2007 to 2021 evaluating HT in primary teeth. Two reviewers independently screened, data extracted and quality assessed the studies. Results: Eleven publications from eight unique studies were included. Four were of low risk of bias overall and five studies were included in a meta-analysis. Overall, HT was 49 % (RR 1.49 [95 % CI: 1.15–1.93], I 2 =89.5 %, p < 0.001) more likely to succeed. When compared to direct restorations, HT was 80 % more likely to succeed; while similar success was found when compared to conventional preformed metal crowns. HT was also over 6 times (RR 0.16 [95 %CI: 0.10–0.27], I 2 =0 %, p < 0.001) less likely to fail. Most of the studies included proximal or multi-surface lesions. Conclusions: HT is successful option for the management of caries in primary teeth, particularly for proximal or multi-surface dentine lesions. It is well-tolerated by children and acceptable to parent, with mild adverse effects reported.